The book graphics of Vilnius printing houses in XVI-XVII centuries - Jolita Liškevičienė (Knygotyra)
The printing activities flourished in Vilnius from the end of the sixteenth century. We may talk about two periods with distinctive features in book illustration in relation to printed book graphics: 1) the end of the sixteenth century to the 1640s; 2) the 1640s to the end of the seventeenth century.